The difference in IL-17 level between mild and severe COVID-19 inpatients of H. Adam Malik General Hospital - Sembiring, Alemmina; Loesnihari, Ricke; Rahmaini, Ade (Jurnal Prima Medika Sains, 2024)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by a new coronavirus, Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2). Pro-inflammatory cytokines play a central role in many viral respiratory infections by coordinating and activating adaptive immune responses. Higher serum levels of pro-inflammatory cytokines (TNF-α, IL-1β, IL-2, IL-6 and IL-17) and chemokines (IL-8) have been observed in many patients with severe COVID-19 compared with individuals with a mild degree. This research is an observational study with cross sectional data collection method. This study took blood samples from mild and severe COVID-19 patients who were treated at the HAM Hospital as many as 34 patients. Samples were examined only once for IL-17 in mild and severe COVID-19 patients. The research was conducted after obtaining ethical approval and informed consent. This study was followed by 18 female subjects (52.9%). The mean age of the subjects was 47.52 years with the youngest age being 23 years old and the oldest being 81 years old. By using the Mann Whitney test, it showed that there was a significant difference in interleukin 17 levels between Covid-19 patients with severe and mild degrees (p = 0.049). IL-17 examination can be used as an alternative diagnostic marker and assess the severity in COVID 19 patients. Further studies are needed that involve a larger number of subjects, and are associated with other inflammatory markers such as CRP or with coagulation status such as D- dimer.